Emotional Dysregulation in Post-COVID Syndrome: Anxiety and Depressive Disorders and the Impact of War - Burdeinyi Андрій (Psychosomatic Medicine and General Practice, 2023)
Relevance. Many patients after COVID-19 continue to suffer from emotional instability, including anxiety and depression, with a negative impact on physical and mental health. Increased stress and difficulties in restoring emotional balance are exacerbated by the war in Ukraine. Both military and civilian individuals affected by the conflict face a double burden of COVID-19 consequences and war stress, making adaptation difficult and reducing self-regulation abilities. Objective. To analyze the current state of emotional dysregulation problems in patients with anxiety and depressive post-COVID disorders, the impact of the large-scale invasion as an additional stress factor, and to understand the possibilities of conducting medical-psychological rehabilitation in the context of remote interaction. Materials and method.: A qualitative and quantitative content analysis and concept analysis was conducted using meta-analyses and systematic reviews of Ukrainian and English-language scientific literature published from January 2019 to September 2023. Conclusions. Post-COVID syndrome symptoms are caused not only by direct contact with the virus but also by other mechanisms such as stress, social isolation, and economic issues caused by the pandemic. The numerous symptoms and development mechanisms of the syndrome complicate its diagnosis and treatment and require a multidisciplinary approach for providing comprehensive medical-psychological assistance and rehabilitation. In the context of post-COVID syndrome, telemedicine and psychological support have become crucial, providing patients with convenient and accessible means of psychological intervention. The war significantly increases the levels of anxiety, depression, and post-traumatic stress disorder among civilians and military personnel. The psychological impact of the war adds new challenges to the already complex situation after COVID-19, emphasizing the need for an integrated approach to providing medical and psychological support where the use of remote technologies for mental health support appears critical, as it can provide psychological support to individuals in dangerous or restricted conditions related to the conflict.